Altered resting-state brain activity in functional dyspepsia patients: a coordinate-based meta-analysis - Mao, Yangke; Zhang, Pan; Sun, Ruirui; Zhang, Xinyue; He, Yuqi; Li, Siyang; Yin, Tao; Zeng, Fang (Frontiers in Neuroscience, 2023)
Background Neuroimaging studies have identified aberrant activity patterns in multiple brain regions in functional dyspepsia (FD) patients. However, due to the differences in study design, these previous findings are inconsistent, and the underlying neuropathological characteristics of FD remain unclear. Methods Eight databases were systematically searched for literature from inception to October 2022 with the keywords “Functional dyspepsia” and “Neuroimaging.” Thereafter, the anisotropic effect size signed the differential mapping (AES-SDM) approach that was applied to meta-analyze the aberrant brain activity pattern of FD patients. Results A total of 11 articles with 260 FD patients and 202 healthy controls (HCs) were included. The AES-SDM meta-analysis demonstrated that FD patients manifested increased activity in the bilateral insula, left anterior cingulate gyrus, bilateral thalamus, right precentral gyrus, left supplementary motor area, right putamen, and left rectus gyrus and decreased functional activity in the right cerebellum compared to the HCs. Sensitivity analysis showed that all these above regions were highly reproducible, and no significant publication bias was detected. Conclusion The current study demonstrated that FD patients had significantly abnormal activity patterns in several brain regions involved in visceral sensation perception, pain modulation, and emotion regulation, which provided an integrated insight into the neuropathological characteristics of FD.